THE EFFECT OF DIGITAL PWM STEADY STATE RESPONSE ON THE SPEED OF BLDC MOTOR - Rahmayanti, Rifa; Utomo, Sapdo; Saputra, Hendri Maja (Teknologi Indonesia, 2015)
This research aims to analyze the work system of a brushless DC (BLDC) motor speed driver. The motor is controlled by a driver which receives speed command signal from a microcontroller. Effect of digital Pulse Width Modulation (PWM) command signal on the speed response of the motor is investigated by changing duty ratio from 30% to 100% and frequency between 500Hz?100kHz. Each speed response is compared against the speed response of the corresponding analog command signal. From the experimental results, it can be concluded that larger switching frequency provides smaller steady state error and smaller standard deviation in the speed response. More specifically, for the BLDC motor used in the experiments, steady state error of 5% rotational speed can be achieved only by a digital PWM command signal the duty cycle ratio of which is larger than 60% and the frequency of which is larger than 1 kHz.